Estimation of Flupentixol in Bulk and Its Pharmaceutical Formulations by Precipitation Reagents - Begum, Jameelunnisa; Rasheed, Abdul (Asian Journal of Chemistry, 2010)
Simple spectrphotometric methods (A-C) for the assay of flupentixol based on the formation of its complexes with alkaloidal precipitants are described. Flupentixol under quantitative precipitation in the form of molecular complexes with iodine (I2, method A), ammonium molybdate (method B) or phosphomolybdic acid (method C) when used in excess. In addition to precipitation reactions, colour reactions have also been combined to estimate flupentixol. They are based on the colour formation with either unreacted precipitant of the filtrate (I2) or released precipitant from the molecular complex (ammonium molybdate or phosphomolybdic acid) with chromogenic reagent such as P-N-methyl amino phenol sulphate (PMAP)-sulphanilic acid (Sac) (for I2), potassium thiocyanate (for ammonium molybdate), cobalt nitrate (Co(II)-disodium salt of ethylene diamine tera acetic acid (EDTA) complex (for phosphomolybdic acid).